THE EFFECT OF THE FRAUD TRIANGLE IN FINANCIAL STATEMENT DETECTION OF FRAUD ON TRANSPORTATION COMPANIES - Tanggor Sihombing; Febry Aditya Nugroho (Universitas Pelita Harapan, 2022)
This research was done to analyze the role of the fraud triangle theory in detecting the occurrence of financial statement fraud of transportation companies listed on S&P Capital IQ and Bursa Efek Indonesia from 2018 through 2020 from 2018 through 2020. The variables tested in this research are financial stability pressure, excessive pressure, personal financial need, financial target, ineffective control, and rationalization. This research uses 162 data from 54 transportation companies on S&P Capital IQ and Bursa Efek Indonesia. The test was done using Stata version 16. It showsed that financial stability pressure, personal financial need, financial target, and independent rationalization variables positively affect the occurrence of financial statement fraud. In contrast, excessive pressure and ineffective control of independent variables hurt the occurrence of financial statement fraud.